2001
DOI: 10.1097/00005537-200107000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Angiosarcoma: A Clinicopathologic Study of Five Cases With a Review of the Literature

Abstract: LA is a rare tumor, frequently associated with previous radiation, usually involving the supraglottis with characteristic histomorphologic and immunophenotypic features. LA has a poor prognosis, making appropriate separation from other conditions important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
(88 reference statements)
0
27
0
Order By: Relevance
“…Despite the fact that the majority of angiosarcomas affect the skin and soft tissues of the head and neck, angiosarcomas within the sinonasal tract account for \0.1% of all malignancies in this region [1,3,[3][4][5][6][7][8][9][10][11][12][13]. This study reports the largest single series of sinonasal tract angiosarcomas reported in the English language to date, with the vast majority of studies reporting only a single case [9,.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite the fact that the majority of angiosarcomas affect the skin and soft tissues of the head and neck, angiosarcomas within the sinonasal tract account for \0.1% of all malignancies in this region [1,3,[3][4][5][6][7][8][9][10][11][12][13]. This study reports the largest single series of sinonasal tract angiosarcomas reported in the English language to date, with the vast majority of studies reporting only a single case [9,.…”
Section: Discussionmentioning
confidence: 97%
“…While angiosarcomas may occur in any region of the body, well over half occur in the head and neck, usually involving the skin and superficial soft tissues, particularly the scalp [1,[3][4][5][6][7]. Despite this fact, angiosarcoma accounts for less than 0.1% of all sinonasal tract malignancies [3,[8][9][10][11][12][13]. Primary sinonasal tract angiosarcomas are exceedingly uncommon and only a few cases have been reported in the English literature [9,.…”
Section: Introductionmentioning
confidence: 99%
“…Loos et al [7] describe five cases of laryngeal angiosarcoma. Of these five cases, the most common site was the epiglottis and four of the patients had received prior radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical vascular lesions (AVL) and angiosarcomas (AS) are lesions known to arise after radiation therapy [1][2][3][4][5][6][7][8][9][10][11][12]. They are most commonly described in the breast region status post radiation for breast carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Loos et al reported five cases of primary angiosarcoma of the larynx with a history of previous radiation in two of their cases, pointing towards radiation being an aetiological factor. 13 LAS is twice more common in men than in women (male-to-female ratio: 2.3:1), with a mean age of 61 years at presentation. [14][15][16][17] It can affect any site in the larynx with the majority being in the supraglottis.…”
Section: Discussionmentioning
confidence: 99%